O roli dvigatel'noj asimmetrii nizhnikh konechnostej v dinamike sportivnykh dejstvij - Ivanova, G. P.; Spiridonov, D. V.; Sautina, E. N. (Teorija i Praktika fiziceskoj Kul'tury, 2003)
The asymmetry of the lower extremities has various displays in sports: difference of the power characteristics of legs by integrated estimations, the power of the same groups of muscles of different extremities, the coordination opportunities etc. The reason of motor asymmetry - the distinction of a degree of participation, or the various role, the right and left hemisphere of a brain in management of movements of extremities and conditions of the life of the person. The training process, certainly, influences the degree of the asymmetry both in the power, and in the coordination. However the functional distinction of legs shown in sports in the specificity of work of a basic and not basic leg, remains always essential and basically constant. It allows to speak about the presence of the special reasons and the physiological mechanisms responsible for the formation of the specified distinctions. The one of such reasons in the opinion of authors - the asymmetry of distribution of masses in the body of the person in the frontal plane concerning its longitudinal axis.